2015
DOI: 10.4236/pp.2015.68041
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Anti-Nutritional Quantification Assessment of <i>Cymbopopgon citratus</i> Leaf

Abstract: The leaf-extract of Cymbopogon citratus was evaluated for nutritional and anti-nutritional compositions. The results revealed that the plant leaves contained appreciable amounts of phytochemicals (alkaloids, glucosides, phenols, saponins, flavonoids and tannins), proximate compositions (proteins, carbohydrates, fats, crude fibre, ash and moisture), vitamins (A, C, E, B1, B2 and B9) and trace elements (Fe, Zn, Mn, Cu, Na, K, Ca and Co) in varying degrees. These chemical compositions obtained may be responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
(9 reference statements)
5
11
0
Order By: Relevance
“…The vitamin concentrations of T. occidentalis grown on gas flared remediated soil were higher than those on non-gas flared soil for 7.1 t ha −1 and 13.9 t ha −1 biochar treated plants, suggesting that 13.9 t ha −1 biochar treatment promoted vitamin synthesis. The result agrees with that of Lou et al [ 29 ] who reported increased vitamin C concentration in cabbage grown with an aqueous extract of maize straw biochar.…”
Section: Resultssupporting
confidence: 93%
“…The vitamin concentrations of T. occidentalis grown on gas flared remediated soil were higher than those on non-gas flared soil for 7.1 t ha −1 and 13.9 t ha −1 biochar treated plants, suggesting that 13.9 t ha −1 biochar treatment promoted vitamin synthesis. The result agrees with that of Lou et al [ 29 ] who reported increased vitamin C concentration in cabbage grown with an aqueous extract of maize straw biochar.…”
Section: Resultssupporting
confidence: 93%
“…Ascorbic acid (Vitamin C) is known for its high antioxidative activity and is essential for proper heart functioning and maintaining skin health. Our result showed that the T. populnea leaf contained 44.3 ± 5.5 mg 100 g −1 DW of ascorbic acid (Table 1), which was higher than the medicinal plant Cymbopogon citratus (Uraku et al, 2015), suggesting that the vitamin C content in the leaves of T. populnea is enough for fulfilling the daily requirements of a healthy individual. Another important antioxidant compound is carotenoids.…”
Section: Vitamins Antioxidants and Antioxidative Enzymesmentioning
confidence: 71%
“…The results of the study showed high concentrations of retinol, niacin and folic acid with low concentration of ascorbic acid and thiamin. The high concentrations of retinol, niacin and folic acid obtained in the study were higher than that obtained from Cymbopogon citratus leaves according to Uraku et al (2015a) [4]. The presence of retinol in high concentrations is an indication that the leaves could be a good source for growth and development, maintenance of immune system and good vision [17,18].…”
Section: Resultsmentioning
confidence: 69%
“…These plants served as an indispensable constituent of human diet supplying the body with minerals, vitamins and certain hormone precursors, in addition to protein and energy [2,3]. However, many of these economical nutritive plants have not been assessed for their nutritional values or are yet to be adequately studied and utilized by human [4]. Culcasia scandens P. Beauv.…”
Section: Introductionmentioning
confidence: 99%